Beyond Inequality: A Novel Measure of Skewness and its Properties - Walter Kraemer; Holger Dette (Center for Economic Studies and ifo Institute (CESifo), 2016)
We show that a recent appendix to the Gini-coefficient to make the latter more sensitive to asymmetric income distributions can be viewed as an abstract measure of skewness. We develop some of its properties and apply it to the US-income distribution in 1974 and 2010.
Keywords: C46; D31; D63; 330; inequality; Gini-index; skewness